Research on two-way intelligent self-service system of electric power business hall applying data compression algorithm - Zhou, Baowei; Lin, Yongxiang; Cao, Sheng; Su, Hongbang; Qi, Xiaoxuan; Zhang, Yaling (Applied mathematics and nonlinear sciences, 2024)
This paper applies a data compression algorithm to designing a two-way intelligent self-service system for an electric power business hall and proposes a multiwavelet embedded zero-tree coding method and compression of electric power data. Based on the multiwavelet transform, a multiwavelet threshold power data compression algorithm is proposed, and the decomposition reconstruction comparison of the multiwavelet transform, and the implementation process of the compression algorithm are discussed. The implementation effect of the electric power intelligent business hall is discussed through the evaluation analysis of the service before and after the intelligent business hall. The results show that the platform operation effect score of the electric power intelligent service management platform project of company H is 0.8723. This paper's platform design and implementation provide useful research references for improving the service quality and efficiency of the electric power business hall.